Peningkatan Pengelolaan Wisata Melalui Pelatihan Service Sequence dan Pengembangan Produk Berbasis Lokal di Astana Joglo Sidomulyo - Wardani, Peni Arianita; Farhan, Muhamad; Rachman, Nur Afni; Nabiha, Achmad Fawwaz; Taufikurrohman, Taufikurrohman (SEJAGAT : Jurnal Pengabdian Masyarakat, 2025)
Sidomulyo Tourism Village, located in Jember Regency, has undertaken various initiatives to enhance its appeal as a tourist destination. One such initiative is establishing a new restaurant, Astana Joglo, with a village café concept. Positioned near the Sendang Tirto Gumitir spring, with scenic views of rice fields and coffee plantations, Astana Joglo represents an innovative addition to the village’s tourism offerings. However, to ensure its success, thorough preparation is essential before its operation, particularly regarding human resources and product offerings. This service project aims to enhance the management of Astana Joglo by providing training in service procedures and local-based product development. The training program is structured in four stages: preparation, socialization, training, and evaluation. It covers two main areas: service sequence and local-based product development. The primary beneficiaries of this program are the young, productive-age members of the Sidomulyo Tourism Village management team. The outcomes of this initiative include improved knowledge and skills among participants and the creation of Standard Operating Procedures (S.O.P.) for services at Astana Joglo. The average pretest score for the knowledge component was 3.65 while the posttest score was 6.2. On the other hand, the result of the skill pretest score was 2.7 while the result of the posttest was 5.8. To ensure the long-term sustainability of the training, a medium-term evaluation and monitoring process will be implemented, with active involvement from the young managers to support the ongoing development of the tourism facility.